The life and times of Jamyang Khyentse Chökyi Lodrö the great biography by Dilgo Khyentse Rinpoche and other stories - Drubgyud Tenzin Rinpoche; Khenpo Sonam Phuntsok (Boulder, Colorado Shambhala, 2017)
"An illustrated biography of one of the most outstanding Tibetan Buddhist masters of the twentieth century. The foremost torchbearer of the ecumenical Rime movement, Jamyang Khyentse Chokyi Lodro (1893-1959) dedicated his life to the study, practice, and propagation of all the schools and lineages that are collectively known as Tibetan Buddhism. The staggeringly long lists of all the teachings he received and passed on testify to his abiding appreciation for all aspects of the Dharma, and his list of students reveals how his influence transcended sectarian boundaries. The first half of this volume presents informal stories by many of Chokyi Lodro's teachers, students, friends, and relatives, collected by Orgyen Tobgyal Rinpoche and translated here into English for the first time. Intimate, funny, and utterly down-to-earth, these stories--supplemented by sixty-one photographs--paint a tender picture of the man behind the great master, introducing readers to the characters and events in his life, and especially the challenges he faced living against the backdrop of the Chinese occupation of Tibet. The second half comprises an English translation of the spiritual biography, or namtar, by Dilgo Khyentse, one of Chokyi Lodro's closest and most brilliant students. In the process of recounting the life and liberation of his beloved guru, Dilgo Khyentse reveals how he saw Chokyi Lodro as the Buddha in the flesh and provides, essentially, a blueprint of the entire path to enlightenment"--
"Under the guidance of Dzongsar Jamyang Khyentse Rinpoche, Jigme Khyentse Rinpoche, and Orgyen Tobgyal Rinpoche.". - Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: ʼJam-dbyangs Mkhyen-brtse Chos-kyi-blo-gros 1893-1959; Sa-skya-pa lamas -- Biography -- China -- Tibet Autonomous Region; Religion -- Buddhism -- Tibetan; Sa-skya-pa lamas -- China -- Tibet Autonomous Region; Biografie -- 1800-1900